Dynamic pricing for passenger groups of high-speed rail transportation. Issue 4 (January 2017) - Xiaoqiang, Zhang; Lang, Ma; Jin, Zhang
Abstract: The widespread high-speed rail has become an important transportation mode for tourists in China, who travel primarily in groups. With more attractive price, railway operators may be able to expand ridership, improve customer satisfaction, and ultimately increase revenue. The traditional pricing method for passenger groups, however, is relatively simple, inflexible, which may lead to profit loss during off-seasons. In order to assist railway corporations in revenue improvement, a dynamic pricing model is provided to determine the optimal price for passenger groups. Numerical experiments show that the proposed method is able to suggest the optimal price for total revenue maximization, subject to the capacity constraint. Highlights: Dynamic pricing: Flexible pricing strategy will attract more passengers and make higher revenue. Passenger group: Passenger groups have greater chances of being eligible for discounted fare. The model uses dynamic pricing with seat inventory control to handle groups and individual travelers.